Experimental and analytical investigation of the effect of external pressure on compressive behavior of concrete-filled steel tube stub columns. (July 2020) - Mohammadnejad, Mohsen; Naghipour, Morteza; Nematzadeh, Mahdi; Elyasi, Majid
Abstract: Nowadays concrete-filled steel tubes (CFTs) are used in many types of structures. In spite of significant advances, the application of this system has not widely adopted in marine structures. While due to the presence of hydrostatic pressure on the body of the tube, outward buckling, which may be considered as one of the weaknesses of the system, could be delayed. Therefore, theoretical and experimental studies were performed to investigate the effects of external pressure on the compressive behavior of circular concrete-filled steel tubes. In this paper, CFT columns with three different diameter-to-thickness (D/t) ratios of 50, 100 and 200 filled with three concrete compressive strength grades of 15, 30 and 45 MPa. The external pressure and axial load were applied to the specimens simultaneously by tri-axial testing set up designed and constructed by the authors. Based on the test results, the external pressure can effectively increase the load-carrying capacity, as well as the ductility of the specimens. Minimum and maximum improvement in ultimate strength were 67% and 308% respectively. Generally effect of external pressure on specimen filled with lower concrete strength was more than others. Finally, a nonlinear finite element (FE) numerical model using the commercial software package ABAQUS is also developed to predict the performance of such columns. The results show that the proposed FE numerical model provides good agreement with experimental data.